Integrating Public Health and Deliberative Public Bioethics: Lessons from the Human Genome Project Ethical, Legal, and Social Implications Program - Meagher, Karen M. (Public Health Rep, 2016)
Public health policy works best when grounded in firm public health standards of evidence and widely shared social values. In this article, we argue for incorporating a specific method of ethical deliberation—deliberative public bioethics—into public health. We describe how deliberative public bioethics is a method of engagement that can be helpful in public health. Although medical, research, and public health ethics can be considered some of what bioethics addresses, deliberative public bioethics offers both a how and where. Using the Human Genome Project Ethical, Legal, and Social Implications program as an example of effective incorporation of deliberative processes to integrate ethics into public health policy, we examine how deliberative public bioethics can integrate both public health and bioethics perspectives into three areas of public health practice: research, education, and health policy. We then offer recommendations for future collaborations that integrate deliberative methods into public health policy and practice.